PENGARUH LABA BERSIH, ARUS KAS OPERASI, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris pada Perusahaan Manufaktur yang listed di Bursa Efek Indonesia) - Nindi Septia One Dhira; Novi Wulandari; Nining Ika Wahyuni (Jurnal Ekonomi Akuntansi dan Manajemen, 2014)
This study aimed to analyze the effect of Net Income, Cash Flow from Operations, and The Size Of The Company To Dividend Policy of manufacturing company listed in Indonesia Stock Exchange (IDX ). Data used in this study is a secondary data from annual financial reports of thirtyseven companies during the four years from 2006-2009. The independent variables are Net Income , Operating Cash Flow, and The Size Of The Company, while the dependent variable is Dividend Policy proxied by the dividend yield. Samples of this research determined using purposive sampling method. To analyze the effect of independent variables to dependent variable, the reseachers use regretion analysis. The test results shows that The Net Income, Operating Cash Flow, And The Size Of The Company Partially Influence The Dividend Policy.